An Experimental Investigation of the Scope of Object Comparative Quantifier Phrases. (17th January 2019) - Syrett, Kristen; Brasoveanu, Adrian
Abstract: Recent investigations of the constraints on the scope of Comparative Quantifier Phrases (CQPs) (Takahashi 2006 ;Mayr & Spector 2012 ;Fleisher 2015 ) have revealed a puzzle: while CQPs give the appearance of behaving like typical generalized quantifier phrases in some environments, they seem to have a more restricted scopal range than other quantificational phrases, apparently resisting inverse scope over indefinite subjects, except in certain discourse contexts. In this paper, we present a set of three experiments probing the scope of object CQPs relative to a singular indefinite in subject position. Based on the results, make two major contributions. First, we demonstrate that CQPs in object position can uncontroversially take wide scope over an indefinite subject, thereby revealing that they have a wider scopal range than has been assumed based on introspection, and than the current decompositional accounts on the market allow. Second, we identify two factors related to processing scopally ambiguous sentences and three specific factors that affect the accessibility availability of the inverse scope reading: the form of the subject indefinite, the form of the object CQP, and the felicity conditions supporting the use of a CQP. Our results thus underscore the features of the optimal contexts for examining the full scopal range of quantificational phrases more generally. We propose that the varied scopal behavior of object CQPs in particular are related to their post-suppositional cardinality requirements (Brasoveanu 2013 ), which interact with independently motivated processing preferences.